Prenatal Diagnosis and Classification of Fetal Hypospadias: The Role and Value of Magnetic Resonance Imaging. Issue 6 (19th February 2021) - Li, Kui; Zhang, Xiaodan; Yan, Guohui; Zheng, Weizeng; Zou, Yu
Abstract : Background: Prenatal diagnosis and classification of hypospadias are difficult and of value for management during perinatal and neonatal periods. The conventional approach for prenatal diagnosis of hypospadias is ultrasound; however, this technique may be inconclusive in certain cases, which prompts for further exploration with magnetic resonance imaging (MRI). Purpose: To investigate the role of MRI in the prenatal diagnosis and classification of fetuses with hypospadias. Study Type: Retrospective. Population: Thirty‐five fetuses (median gestational age = 37, range 24–39 weeks) with possible hypospadias. Field Strength/Sequence: Single‐shot fast spin echo T2‐weighted imaging, fast imaging employing steady‐state acquisition (FIESTA), and three‐dimensional FIESTA acquired at 1.5 T. Assessment: Diagnosis and classification of hypospadias using MRI were performed by three experienced radiologists based on MRI features, including a short penile shaft, abnormal penile tip, penile curvature, bifid scrotum, "tulip sign, " and penoscrotal transposition. The accuracy of MRI in the diagnosis and classification of hypospadias was assessed in comparison to postnatal clinical diagnosis. The interobserver agreement between radiologists was also assessed. Statistical Tests: Kendall's W test was applied to assess the interobserver agreement between radiologists. Taking postnatal clinical diagnosis as the reference standard, the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were calculated. Results: Of the 35 fetuses, 24 cases were confirmed as hypospadias through postnatal clinical diagnosis. The interobserver agreement between radiologists was substantial (Kendall's W  = 0.781, P  < 0.001). Of the 24 confirmed cases (13 cases of severe hypospadias and 11 cases of mild hypospadias), 22 cases were correctly diagnosed by MRI. The accuracy of MRI in the diagnosis of hypospadias, severe hypospadias, and mild hypospadias was 85.71%, 82.86%, and 80.00%, respectively. Data Conclusion: MRI has good performance in the diagnosis of fetal hypospadias. In addition, MRI could help evaluate the severity of fetal hypospadias. Level of Evidence: 3 Technical Efficacy: Stage 2